Solidification of gray cast iron - Rivera, Graciela Leonor (2004)
This article investigates the solidification of hypo, eutectic and hypereutectic gray cast irons, using novel techniques developed by the authors. The nature of the revealed macro and microstructure suggests that the solidification mechanism is different from that usually accepted.